The Oxford illustrated history of modern China - Wasserstrom, Jeffrey N. (Oxford University Press, 2016)
This lavishly illustrated volume explores the history of China from the founding of the Qing Dynasty (1644-1912) through to the present day. Essential reading for anyone who wants to understand this rising superpower on the verge of what promises to be the 'Chinese century'.